Technoeconomic Comparison of Scenarios for the Configuration of the Renewable Hydrogen Supply Chain in Colombia - Erazo-Cifuentes, Yovany Arley; Orejuela, Juan Pablo; Manotas-Duque, Diego F. (International Journal of Energy Economics and Policy, 2022)
Green hydrogen (RH2) can be used as a clean fuel and as energy vector. For this reason, it is a promising solution to the problems faced by the renewable energy (RE) industry. One determining factor for achieving its practical implementation is the correct configuration of its supply chain. This study compares different hydrogen supply chain (HSC) configurations. RH2 production will be by water electrolysis using RE in the Colombian Caribbean region, then, converted into Liquid Organic Hydrogen Carrier (LOHC), Cryogenic Liquid Hydrogen (LH2) or Compressed Hydrogen Gas (GH2), later, transported by trucks and delivered to meet the projected demand of the transportation sector. In the reference scenario, we found that the best alternative is to produce RH2 using an AEC-type electrolyser (alkaline electrolysis cells) powered by wind energy and convert it to GH2 at 350 bar for transportation and storage. Then, scenarios of demand, one-way distance and WACC were considered for projections between 2030 and 2050. The results showed that can be determined the one-way distance from which converting and transporting RH2 as LOHC is the best alternative and, also can be determined this limit for demand values, which allows us to identify the best configuration of the HSC.